English language support for newcomer learners in Irish primary schools : a review and case study - Kirwan, Déirdre (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2009)
The first part of this thesis (Chapters One to Four) highlights changes that have occurred in the Irish educational system in the last ten to fifteen years in relation to English as a Second Language (ESL) teaching and learning and discusses the role played by the Department of Education and Science (DES) in response to these changes. This includes the establishment of Integrate Ireland Language and Training (IILT) and its engagement with the primary school sector in developing expertise and strategies for dealing with the needs of ESL learners in the education system. Literature relevant to the area of Second Language Acquisition (SLA) and primary school pedagogy is reviewed and Scoil Bhríde Girls' School is described as the setting within which the research in question takes place. The thesis begins by examining features of SLA and how they impinge on four groups of ESL learners in an Irish primary school. The relevance of personal construct theory is examined from the perspectives of both language learning and pedagogy. The theories of Barnes (1976) and Bruner (1966; 1975; 1977) are of particular relevance as is the view of Little (1991; 2007a; 2007b) in relation to the notion of learner autonomy. The importance of literacy in the development of both language and cognitive functioning is also presented. Chapter Two examines the role of the DES in terms of provision made for dealing with the challenges of ESL pupils in primary school classrooms. The importance of mother tongue in the development of second language skills is considered as are the challenges in relation to the diversity of L1s is that are found not only in primary schools generally, but also in individual classrooms. The distinction between surface and complex language is explored and its relevance to learning is emphasized. Implications for teacher training are also addressed. Chapter Three is focused on the work of IILT whose terms of reference included an analysis of the demands of the primary curriculum and the provision of both expertise and support for teachers working with ESL pupils. The development of English Language Proficiency Benchmarks that reflect the primary curriculum and the European Language Portfolio (ELP) for use in primary schools are discussed, among other elements, as key features of the work accomplished by IILT. In Chapter Four, the challenges experienced in dealing with the inclusion of ESL pupils and the increasing diversity of the school are presented. Factors that impinge on language learning and the creation of a school environment where the needs of all who attend, including indigenous Irish and newcomers, are recognised and met are examined. Challenges for the future are also presented. The procedures and methodology employed in this research are outlined in Chapter Five. This involved the collection, description, analysis and interpretation of linguistic data obtained from four groups of ESL learners at three week intervals during the course of the school year 2005-06. Chapters Six, Seven and Eight deal with the data from terms 1, 2 and 3 respectively. In each case the data is analysed and the progress of individual learners is described in terms of the English Language Proficiency Benchmarks. Chapter Nine comprises the final part of the thesis. Here, conclusions drawn from the analysed data are presented in the light of the reviewed literature, current professional teaching practice and DES supports. The progress of individual learners is discussed in terms of the factors that impinge both positively and negatively on their attempts to leam English and gain access to the primary curriculum. The thesis concludes by making suggestions as to further possibilities for research.
Keywords: Language and Communication Studies, Ph.D.; Ph.D. Trinity College Dublin 2009